A Critical Review of Dhamani Sharir in the Modern Perspective - Singhal, Tina; Srivastava, Nidhi; Srivastava, Ravi; Kumar, Ajay (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda is a treasure trove of information developed and discovered by our forefathers. To fully comprehend and apply the concept of dhamani sharir, we must first understand Sharira. For students of any system of medicine, understanding of Rachana Sharira (anatomy) is required. Srotas, Siras, and Dhamani are terms from the Vedas. The terms Siras and Dhamani is referred to blood vessels in general. However, according to commentators, Dhamani is a thick blood vessel connecting to the heart, and sira is a thin blood vessel. According to Sushruta, ten Dhamani spread upward, ten downward, and four sideward emerging from the nabhi. According to Charak, hridaya produces ten Dhamani. Dhamanis (arteries) described in Ayurveda represent a tubular channel taking origin from the Hridaya(heart) and possess the characteristics of pulsation and circulation of Rasa (lymph chyle or plasma) and Rakta (blood) throughout the body. The up-coursing Dhamani prefers to maintain the body’s integrity by performing particular body functions such as sound, touch, taste, smell, sneezing, laughter, speech, and so on. The Dhamanis that come down establish a pathway for Vata, urine, excrement, semen, and contained food to flow downward. The Tiryaggami-Dhamani can be taken as the cutaneous or peripheral vessels supplying the superficial and deep layers of the skin. This essay will assist in learning more about Dhamanis through ancient science.